Young feminists working globally to end violence against women and girls: key challenges and ways forward. Issue 3 (2nd September 2018) - Homan, Christine; Chandran, Divya; Lo, Rita
ABSTRACT: Drawing from our experience as young feminists working with an emerging feminist advocacy collective focused on addressing violence against women and girls (VAWG), our article focuses on some of the key challenges young feminists face while advocating for feminist-informed programming in efforts to address VAWG in humanitarian and development settings. Drawing on our own experience as young feminists to prevent and address VAWG in a patriarchal world, we see ourselves as walking a tightrope. On one hand, our radical activism is instrumental in achieving a world where no one is left behind. Yet we are often told, in direct and indirect ways, to dial down the feminism, to be 'inclusive' and 'intersectional' with limited meaningful accountability to women and girls. We conclude by offering a set of recommendations aimed at advancing young feminist activism in VAWG work and retaining a feminist space that is political, while working in partnership with other movements and actors.